Pro Apache Beehive - Mittal, Kunal (Apress, 2012)
Welcome to Pro Apache Beehive. SOA and Web Services are finally coming to the forefront of the IT industry. Most companies, large and small, are talking about these technologies and planning a course to adopt them. And J2EE development is still on the front lines for large, mission-critical applications. The Apache Beehive project introduces several new technologies that simplify J2EE development as well as make your applications more service oriented. Beehive provides a layer of technologies that build on the annotations that were introduced in Java 1.5. (Think of annotations as deployment descriptors but in your code instead.)